Fish and invertebrate community response to flow magnitude in the Kansas River - Gerken, Joseph Edward (Kansas State University, 2015)
River discharge influences fish and invertebrate communities and understanding how hydrologic variables contribute to fish and invertebrate composition can provide information for restoration and management. This study examines the relationship between several flow regime metrics that may influence fish and invertebrate community structure in large river systems such as the Kansas River. First, I examined how hydrology influences macroinvertebrate (drifting and benthic) density and fish communities before, during, and after flooding in both main and secondary channels. I found that drifting invertebrate density increased during flooding potentially providing increased prey opportunities for fishes. I also found that fluvial dependent and generalist fish species use inundated habitats more than fluvial specialists. My results suggest that the flux of water into inundated habitats supports a unique subset of invertebrate and fish communities of the main channel. Next, I examined the importance of lateral connectivity on fish and invertebrate composition by examining differences in seasonally and permanently inundated secondary channels in relation to main channel reaches. I found that drifting and benthic invertebrate assemblages and fish assemblages differed between seasonally inundated and permanently connected secondary channels. These results suggest that maintenance of diverse secondary channel connections is useful in preserving native biota in the Kansas River. Finally, I tested if hydrologic variables influenced recruitment of four native Kansas River fishes. I found that recruitment for two of the four fish species (flathead catfish, Pylodictis olivaris, and shovelnose sturgeon, Scaphirhynchus platorynchus) increased in high flow years. These results indicate that a natural and variable flow regime may be important for maintaining fish community structure in the Kansas River. The results of this study have implications for management strategies that include the use of high flows to provide a pulse of insect prey to the main channel for fishes, restoration of natural high and low flow variability as important to fish recruitment, and diversity in secondary channel connectivity (seasonal and permanently connected) that promotes unique fish and invertebrate communities.
Keywords: Lateral connectivity; Flood; Flood pulse concept; Fish; Invertebrate; Kansas river; Biology (0306); Ecology (0329); Fisheries and Aquatic Sciences (0792)